Reinstatement of Hellwigia Warb. (Zingiberaceae) and its molecular and morphological delimitation - Seni Kurnia Senjaya; Axel Dalberg Poulsen; Marlina Ardiyani; Quentin C.B. Cronk (PhytoKeys)
The currently polyphyletic genus Alpinia Roxb. (Zingiberaceae) has over 260 species widely spread through subtropical and tropical Asia and a complex taxonomic history. This study focuses on the “Carolinensis” clade of Alpinia hitherto suggested by molecular evidence. We expand on previous research through more comprehensive taxon sampling (about a fivefold increase) and morphological observation. We inferred maximum likelihood (ML) and Bayesian trees based on the nuclear ribosomal internal transcribed spacer (ITS) region, using sequences available on GenBank along with 70 newly generated sequences from this study. Our main findings are as follows: (1) ITS provides a convenient marker for separating members of this clade from other Alpinieae. (2) Phylogenetic reconstruction strongly supports the monophyly of the Carolinensis clade. (3) We identify four subclades with relatively distinct geographical distributions. (4) We determine that morphologically the clade is characterized by inflorescences having densely packed flowers arranged on lateral monochasial cymes, tubular bracteoles, and flowers with oblong or linear labella. (5) The clade is apparently restricted to the east of Huxley’s biogeographic line. These findings support the recognition of the Carolinensis clade as a distinct genus. Hellwigia Warb. is the oldest valid name for this lineage, and till the present paper only includes H. pulchra Warb. We present a generic circumscription of the genus comprising 76 species to date placed in Alpinia. In the present paper, we make 76 new combinations and designate 26 lectotypes. The eastern distribution of the clade offers insights into historical biogeographic barriers and lineage diversification. As such, Hellwigia represents an interesting model for exploring evolutionary and ecological processes in this region, and future phylogenomic studies will be critical for resolving remaining phylogenetic uncertainties and for deepening our understanding of the evolutionary dynamics in this unique lineage.